The two-faced role of RNA methyltransferase METTL3 on cellular response to cisplatin in head and neck squamous cell carcinoma in vitro model - Ostrowska, Kamila; Rawłuszko-Wieczorek, Agnieszka A.; Ostapowicz, Julia; Suchorska, Wiktoria M.; Golusiński, Wojciech (Frontiers in Oncology, 2024)
Background RNA methyltransferase-like 3 (METTL3) is responsible for methyl group transfer in the progression of N6-methyladenosine (m6A) modification. This epigenetic feature contributes to the structural and functional regulation of RNA and consequently may promote tumorigenesis, tumor progression, and cellular response to anticancer treatment (chemo-, radio-, and immunotherapy). In head and neck squamous cell carcinoma (HNSCC), the commonly used chemotherapy is cisplatin. Unfortunately, cisplatin resistance is still a major cause of tumor relapse and patients’ death. Thus, this study aimed to investigate the role of METTL3 on cellular response to cisplatin in HNSCC in vitro models. Materials and methods HNSCC cell lines (H103, FaDu, and Detroit-562) with stable METTL3 knockdown (sgMETTL3) established with CRISPR-Cas9 system were treated with 0.5 tolerable plasma level (TPL) and 1 TPL of cisplatin. Further, cell cycle distribution, apoptosis, CD44/CD133 surface marker expression, and cell’s ability to colony formation were analyzed in comparison to controls (cells transduced with control sgRNA). Results The analyses of cell cycle distribution and apoptosis indicated a significantly higher percentage of cells with METTL3 knockdown 1) arrested in the G2/S phase and 2) characterized as a late apoptotic or death in comparison to control. The colony formation assay showed intensified inhibition of a single cell’s ability to grow into a colony in FaDu and Detroit-562 METTL3-deficient cells, while a higher colony number was observed in H103 METTL3 knockdown cells after cisplatin treatment. Also, METTL3 deficiency significantly increased cancer stem cell markers’ surface expression in all studied cell lines. Conclusion Our findings highlight the significant influence of METTL3 on the cellular response to cisplatin, suggesting its potential as a promising therapeutic target for addressing cisplatin resistance in certain cases of HNSCC.